Inducible Conditional Vascular-Specific Overexpression of Peroxisome Proliferator-Activated Receptor Beta/Delta Leads to Rapid Cardiac Hypertrophy. (3rd March 2016) - Wagner, Kay-Dietrich; Vukolic, Ana; Baudouy, Delphine; Michiels, Jean-François; Wagner, Nicole
Abstract : Peroxisome proliferator-activated receptors are nuclear receptors which function as ligand-activated transcription factors. Among them, peroxisome proliferator-activated receptor beta/delta (PPAR β / δ ) is highly expressed in the heart and thought to have cardioprotective functions due to its beneficial effects in metabolic syndrome. As we already showed that PPAR β / δ activation resulted in an enhanced cardiac angiogenesis and growth without impairment of heart function, we were interested to determine the effects of a specific activation of PPAR β / δ in the vasculature on cardiac performance under normal and in chronic ischemic heart disease conditions. We analyzed the effects of a specific PPAR β / δ overexpression in endothelial cells on the heart using an inducible conditional vascular-specific mouse model. We demonstrate that vessel-specific overexpression of PPAR β / δ induces rapid cardiac angiogenesis and growth with an increase in cardiomyocyte size. Upon myocardial infarction, vascular overexpression of PPAR β / δ, despite the enhanced cardiac vessel formation, does not protect against chronic ischemic injury. Our results suggest that the proper balance of PPAR β / δ activation in the different cardiac cell types is required to obtain beneficial effects on the outcome in chronic ischemic heart disease.